Science with character: Teachers’ reflections on the Pancasila student profile initiative - Marlina, Reni; Yuenyong, Chokchai; Hamdani, Hamdani; Zubir, Aminah (Universitas Muhammadiyah Surakarta, 2026)
This study investigates science teachers’ perspectives, beliefs, and readiness in implementing the Pancasila Student Profile Strengthening Project (P5) within the Merdeka Curriculum in Indonesian junior high schools. The study involved 102 science teachers from public junior high schools in West Kalimantan who participated in the School Mover Program (PSP). Using a mixed descriptive approach, data were collected through a validated Likert-scale questionnaire and open-ended responses, and analyzed using descriptive statistics and Exploratory Factor Analysis (EFA). The results reveal that science teachers generally perceive the P5 project as valuable for connecting scientific concepts with real-world environmental and social issues, fostering collaboration, reflection, and contextual learning. Teachers believe that the project enhances students’ scientific literacy, environmental awareness, and ethical responsibility, and aligns well with experiential learning, contextual teaching, and education for sustainable development. However, despite these positive beliefs, several inhibiting factors limit effective implementation. Major constraints include limited instructional time, lack of project design skills, insufficient teaching materials, uncertainty in assessing moral-ethical dimensions, and low confidence in students’ readiness to engage in project-based science learning. In addition, school science culture, which strongly emphasizes cognitive achievement and examination performance, further constrains teachers’ willingness to prioritize project-based approaches. The findings indicate a clear gap between teachers’ positive attitudes toward the P5 initiative and the practical challenges they face in classroom implementation. This study highlights the critical role of teacher professional development, curriculum support, and instructional innovation in ensuring the sustainability and effectiveness of this innovative learning model within science education. By addressing these structural and pedagogical barriers, the P5 project has strong potential to become a model of transformative and innovative learning, integrating scientific understanding, character education, and sustainable development within the Merdeka Curriculum.